Age and reproduction of the southern king croaker menticirrhus americanus in subtropical south atlantic environments - de Carvalho, Barbara Maichak (2021)
Menticirrhus americanus were sampled (n = 393) from two beaches (P1 is an estuarine beach near the mouth of the Paranaguá Estuarine Complex, and P2 is a beach adjacent to the Paranaguá Estuarine Complex) in the subtropical region of the western South Atlantic waters between August 2015 and June 2016. This study aimed to identify the spawning season and the age structure for M. americanus using two sampling methods. For sampling at the P1 beach, seine, line, and pole were used, while samples from the P2 beach were obtained from the artisanal fishers. Females were numerically dominant in all sampling months at both sites except for February when the males became dominant. The species exhibited a protected reproductive season with multiple spawning peaks between August and December. Males and females were captured at all gonadal development stages and ages between 1 and 6 from both sites. At first maturity, the length of the females was 16.3 cm, and the mean age at first maturity was 1.3 years. Individuals aged between 1 and 3 years were dominant (68%). The results suggested that young and adults of the M. americanus use the same habitats throughout their ontogeny.